BUDIDAYA PADI PADA LAHAN SAWAH BUKAAN BARU WILAYAH PERBATASAN KABUPATEN MERAUKE - Petrus A Beding; Fransiskus Palobo; Batseba MW Tiro (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2019)
Merauke Regency is one of the districts in Papua Province which borders directly with neighboring Papua New Guinea (PNG), which in addition is a rice development area. In general, new openings, poor physical and chemical properties with porous soils, thin layer, low organic matter content, high salinity and drought problems. This study aims to determine the productivity of rice in new openings in the border region. The study was conducted in Merauke Regency, Papua Province from April to August 2018. The design used was a factorial Randomized Block Design with 5 factor children, each variety used was Inpari-32, Inpari-33, Inpari-43, Inpara-8, Dodok Erok. The results of the study were acid soil pH status, high and very high organic matter, very low cation exchange rate. The components of growth in plant height, productive tillers and panicle length were not significantly different. The yield component was significantly different in the highest number of unripe per-panicle Inpara-8 (140.3 g), the highest empty grain per panicle Inpara-8 (55.5 grains) and the 1000 heaviest Dodok Erok 29.4 g. Whereas Grain content, Dry Grain Harvest is not real.